Pemberian Diet dan Rebusan Kelor dengan Masalah Ketidakseimbangan Nutrisi pada Lansia Diabetes Melitus - Tutik Yuliyanti Tutik Yuliyanti; Muhammad Lingga Nur Alim (Politeknik Kesehatan Bhakti Setya Indonesia, 2022)
Management of diabetes mellitus with diet therapy, exercise, education and counseling can prevent complications so that patients can live healthy lives. Giving diet and boiled Moringa leaves can meet daily nutritional needs and reduce blood sugar levels. The purpose of this study is to describe the management of diet administration and Moringa leaf decoction with the problem of nutritional imbalance less than the needs of the elderly with diabetes mellitus. The design of this research is descriptive qualitative: a case study using the nursing process approach. The technique used in this study uses non-probability sampling with a purposive sampling approach. The results of the study showed that the subject's assessment data said that they were weak, ate half a portion, lacked interest in eating, weak general condition, decreased skin turgor, pale face, anemic conjunctiva, dry lips, underweight, BMI in the thin category (17-18) GDS: 320 -375mg/dl. The nursing diagnosis is nutritional imbalance less than requirements. The planning that is set is the provision of diet and Moringa leaf stew. Researchers carried out nursing actions for 14 days with 3 actions every day. The evaluation found that the subject said he ate the menu served and finished it, the subject looked fresh and ate and drank the portion served, elastic skin turgor, moist mucosa, reddish conjunctiva, moist lip mucosa, Moringa leaf concoction was drunk and finished it, BMI:16-18 in the category thin, BW: 42.2-49.2kg, GDS: 214-235mg/dl. Conclusion: giving diet and decoction of Moringa leaves can overcome the problem of nutrition less than the body's needs in the elderly with diabetes mellitus Keywords: diet, Moringa leaf stew, nutrition, diabetes mellitus